2013
DOI: 10.1175/jtech-d-12-00150.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Improvement of an Iterative Scattering Correction Scheme for in situ Absorption and Attenuation Measurements

Abstract: The performance of several scattering correction schemes for reflecting-tube absorption and beam attenuation measurements is evaluated with data collected in European shelf seas. Standard scattering correction procedures for absorption measurements perform poorly because of nonzero absorption in the near infrared and wavelength-dependent scattering phase functions. A previously described iterative correction procedure based on Monte Carlo simulations of the Western Environmental Technologies Laboratories (WET … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 37 publications
0
40
0
Order By: Relevance
“…The reflective tube technology is well established as an industry standard for in situ measurements of spectral absorption (NASA Protocols [9]). In light of recent improvements in scattering correction approaches for AC-9/s instruments [16,18], it seems timely to revise and quantify uncertainties associated with AC-9/s absorption measurements beyond scattering errors. The PSICAM technique, on the other hand, is much less widely used because its operation is laborious, despite its potential to produce absorption data that is effectively free from systematic scattering artefacts.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The reflective tube technology is well established as an industry standard for in situ measurements of spectral absorption (NASA Protocols [9]). In light of recent improvements in scattering correction approaches for AC-9/s instruments [16,18], it seems timely to revise and quantify uncertainties associated with AC-9/s absorption measurements beyond scattering errors. The PSICAM technique, on the other hand, is much less widely used because its operation is laborious, despite its potential to produce absorption data that is effectively free from systematic scattering artefacts.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is not possible to determine the true absorption coefficient of a sample, given its relatively high precision and absence of systematic scattering error, PSICAM data has previously been used as a reference for validating other absorption measurements [16,18,31]. Results showed that AC-9/s data typically overestimate PSICAM absorption across the representing average estimates of accuracy statistics for AC-9 and AC-s data respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations